2005
DOI: 10.1111/j.1540-4560.2005.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in a Post‐Affirmative Action World

Abstract: Mentoring can be an effective strategy in improving retention of college students and faculty from fields where historical underrepresentation has occurred. This article reviews the benefits of mentoring in higher education, and identifies components of effective mentoring strategies that promote educational and career advancement. It illustrates how effective programs can be institutionalized and scaled through consortial and national collaborations. Traditional and alternative mentoring models are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 38 publications
2
115
0
3
Order By: Relevance
“…Programs that aim to address deficits are not unusual and, though wellintentioned as support, have been of particular concern to women and minorities. Boice (1993 p306) found that "women were more inclined to see offers of help as problematically manipulative or intrusive" and Girves, Zepeda and Gwathmey (2005) felt that "[w]omen and minorities... may feel uncomfortable with the concept of being groomed or cloned fearing they must give up their own identities. ... [mentees] may be reluctant to seek out mentors out of fear that they will be perceived as being too dependent" (Girves et al 2005 p456).…”
Section: An Individualised Process For Menteesmentioning
confidence: 99%
“…Programs that aim to address deficits are not unusual and, though wellintentioned as support, have been of particular concern to women and minorities. Boice (1993 p306) found that "women were more inclined to see offers of help as problematically manipulative or intrusive" and Girves, Zepeda and Gwathmey (2005) felt that "[w]omen and minorities... may feel uncomfortable with the concept of being groomed or cloned fearing they must give up their own identities. ... [mentees] may be reluctant to seek out mentors out of fear that they will be perceived as being too dependent" (Girves et al 2005 p456).…”
Section: An Individualised Process For Menteesmentioning
confidence: 99%
“…Personal challenges include work/life balance [6][7][8] and childbearing and child rearing decisions. Workplace issues include lack of mentoring [9][10][11], feelings of marginalization or isolation [16,[20][21][22], and the lack of sponsorship by senior colleagues [12,13]. While the findings of the self-study are in line with other findings regarding women faculty in STEM, the current AdvanceRIT project seeks to disrupt the existing sluggish processes and practices on campus to accelerate and increase the attainment of project goals.…”
Section: Introductionsupporting
confidence: 79%
“…Other studies have confirmed the relationship of having a network of mentors compared to just a single mentor will enhance career success and personal well-being (de Janasz, 2004;Girves, 2005;Johnson, 2007). In a study by van Emmerik (van Emmerik, 2004), it was found that having multiple mentors is not a substitute for a single mentor but should be held in addition to a core relationship.…”
Section: B Mentoring Constellationsmentioning
confidence: 95%